Kajian Prinsip dan Elemen Desain Arsitektur Nusantara - Raden Mohamad Wisnu Ibadi; Josef Prijotomo (CV. Gio Architect, 2023)
Nusantara architecture ('original' Indonesian architecture) has differences and similarities compared to European Architecture. One of the reasons for this difference is the geographical and climatology conditions of Indonesia which is located on the equator line has 2 seasons, namely the rainy season and the dry season. While the European continent is located above the equator, divided into northern, western, eastern and central Europe and most European countries have 4 seasons in a year, namely spring, summer, autumn and winter. Geographical and climatology differences coupled with differences in living patterns and behavior as well as the culture of the people, cause differences in the mindset of Archipelago Architecture from European Architecture. The oral tradition left many of the noble cultural values of the Indonesian people behind the written traditions of European culture, coupled with the Dutch colonial rule that made the European mindset be practiced in the world of modern Indonesian architecture today. There is a lack of writing and research related to the Nusantara mindset which inspire this paper to examines the elements and design principles of Nisantara Architecture in an exploratory and speculative way compared to the European mindset. The objective of the research is to identify the applicability and inapplicability of design elements and principles of European-classic architecture in the Batak Karo architectural environment.